The expressions for each of the given statements are
a. 6 + z
b. 20 - x
c. x/6 - 8
d. x + 5/4
<h3>Writing an expression </h3>
From the question, we are to write an expression for each of the given statement
a. the sum of 6 and z
That is,
6 + z
b. the difference between 20 and x
That is,
20 - x
c. 8 less than the quotient of x divided by 6
That is,
x/6 - 8
d. x increased by 5 divided by 4
That is,
x + 5/4
Hence, the expressions for each of the given statements are
a. 6 + z
b. 20 - x
c. x/6 - 8
d. x + 5/4
Learn more on Writing an expression here: brainly.com/question/17651563
#SPJ1
Given,
The sum of three integers is 92
So,
Let,
The first integer be "x"
The second integer be "y"
The third integer be "z"
Now,
According to the question,
y = 3x ..............equation (1)
z = 2x - 10 .............. equation (2)
x + y + z = 92 ..............equation (3)
Now,
Substituting the value of "y" and "z" from equation (1) and (2), we get,
x + (3x) + (2x - 10) = 92
x + 3x + 2x - 10 = 92
6x - 10 = 92
6x = 92 + 10
x = 102 / 6
x = 17
Now,
substituting the value of "x" in equation (1)
y = 3 (17)
y = 51
Now,
Substituting the value of "x" in equation (2),
z = 2 (17 ) - 10
z = 34 - 10
z = 24
So, the numbers are 17, 51 and 24
NEVER HATE MATH!!!
Answer:
k=4
Step-by-step explanation:
An algebraic expression is, obviously, an expression with a variable.
"A number" would represent a variable, which, in this case, we'll use y.
So, 15 decreased by twice x.
15 - y x 2 =
I hope this helped :)
Standard form is
ax + by = c
Only choice A is in that form.